2021
DOI: 10.1155/2021/5577610
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Effect of Rhizoma coptidis on Polycystic Ovary Syndrome Based on Network Pharmacology and Molecular Docking

Abstract: Background. Rhizoma coptidis (RC) showed a significant effect on PCOS, but its mechanism in PCOS remains unclear. Methods. The components of RC were searched by TCMSP. The Smiles number of the active ingredients was queried through PubChem, and the predicted targets were obtained from the SwissTargetPrediction database. The DrugBank, GeneCards, and DisGeNET databases were retrieved to acquire the related targets of PCOS. Then, the network of compound-target was constructed. The core targets were analyzed using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 71 publications
0
0
0
1
Order By: Relevance
“…Previous studies have shown that calcium acts as a second messenger in most species and all mammals, that calcium signalling can restore oocyte meiosis and activate the egg, which is essential for the regulation of embryonic development [48,49], and that the activation of calcium signalling pathways can inhibit follicular atresia [50]. cAMP signals can regulate the excitability of gonadotropin-releasing hormone (GnRH) neurons [51,52]. GnRH regulates the levels of female reproductive hormones such as luteinising hormone, which affects ovulation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that calcium acts as a second messenger in most species and all mammals, that calcium signalling can restore oocyte meiosis and activate the egg, which is essential for the regulation of embryonic development [48,49], and that the activation of calcium signalling pathways can inhibit follicular atresia [50]. cAMP signals can regulate the excitability of gonadotropin-releasing hormone (GnRH) neurons [51,52]. GnRH regulates the levels of female reproductive hormones such as luteinising hormone, which affects ovulation.…”
Section: Discussionmentioning
confidence: 99%
“…Hal ini dapat menyebabkan siklus menstruasi menjadi tidak teratur disertai jumlah folikel kista (Cystic Folicle) yang terbentuk meningkat. Dengan demikian, ovarium yang mengalami PCOS memiliki bobot yang lebih berat jika dibandingkan dengan ovarium normal (Rajan et al, 2017;Hong et al, 2019;Qiu et al, 2019;Shaaban et al, 2021;Duan et al, 2021). Selain perubahan kadar hormon, juga terjadi gangguan toleransi glukosa (impaired glucose tolerance/IGT) pada wanita yang mengalami PCOS secara substansial kadar glukosa lebih tinggi bila dibandingkan dengan wanita tanpa PCOS yang sesuai dengan usia dan bobot badan (Qiu et al, 2019).…”
Section: Pendahuluanunclassified